"Non hai noite tan longa": Investigation, History and Memory of the Last Francoism - Rivadulla Costa, Diego (Madrygal. Revista de Estudios Gallegos, 2018)
The novel Non hai noite tan longa by Agustín Fernández Paz, published in 2011, explores the recent francoist past, trying to understand it from a current perspective by reflecting on how necessary it is to the memory and reparation of the victims of the dictatorship. This paper proposes an interdisciplinary analysis that focuses on the relevance of the use of the detective story to explore the past and on the realistic and critical recreation of the late-francoist society. Last but not least, the paper highlights the emphatic message about recovering historical memory given by this novel.
Keywords: Agustín Fernández Paz; Memory; Francoism; Galician Narrative; Memory Novel.